Uji Daya Hambat Jamur Eksofit terhadap Phytophthora palmivora (Butler) Butler Penyebab Penyakit Busuk Buah Kakao secara In Vitro - WIBOWO, ONGKY ARI; SUDARMA, I MADE; PUSPAWATI, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
In Vitro Inhibition Test of Exophytic Fungi against Phytophthora palmivora (Butler) Butler the Cause Black Pod Disease on Cocoa Cocoa is one of the featured crop plantations in indonesia. In a development widely, a common problem is black pod disease. In indonesia Phytophthora palmivora fungi is a major cause black pod disease of cocoa. This disease can reduce the yield and quality of cocoa up to 32-99%.The use of microbial antagonists as a biocontrol agent to suppress the growth of P. palmivora is important. Some exophytic fungi known to have high potential antagonists in suppressing the growth of P. palmivora fungi. This study was aims to determine the potential inhibition of exophytic fungi in suppressing the growth of P. palmivora fungi in vitro. This research was conducted in July 2016 to October 2016 at the laboratory of Biotechnology, Faculty of Agriculture, University of Udayana. Stages of the research include: isolation of pathogenic fungi, isolation exophytic fungi, an in vitro test, and identification of fungi. The result showed the pathogen P. palmivora the cause black pod disease of cocoa at Perean Village, Tabanan Regency, Bali. Exophytic fungus which has the potential inhibition of the highest in study include: Rhizoctonia sp. 93,7%, Trichoderma sp1. 92,9%, Rhizopus sp. 94,4%, Aspergillus sp. 88,2%, Trichoderma sp2. 94,8%, Mucor sp. 93,7%. Exophytic fungi which has antibiosis substance is Trichoderma sp1.